Sustainable Strategies to Reduce Water Pollution from Domestic Wastewater Discharge - Ridwan, Ridwan; Tang, M; Syafri, Syafri; Jumain, Aslam; Akrim, Djusdil; Buraerah, Muh. Fikruddin; Wellang, Marini Ambo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Urban rivers are increasingly threatened by pollution from domestic and industrial waste, leading to water quality degradation. The Pampang River in Makassar, an essential water source for residential, agricultural, and industrial use, faces growing pressure from untreated wastewater discharge. This study evaluates the current water quality status of the Pampang River by analyzing BOD, COD, pH, and temperature, and projects future pollution trends using predictive modeling. Water samples were collected from six strategic locations along the river to represent various pollution sources. BOD and COD were analyzed according to SNI 6989.72:2009 and SNI 6989.02:2019, while pH and temperature were measured in situ. A time series regression model predicted pollution levels over the next five years. Results indicate BOD (4.426–6.439 mg/L) and COD (34.1594–43.4827 mg/L) remain within regulatory standards but show an upward trend, potentially exceeding acceptable limits in 3–4 years. pH (7.39–8.08) and temperature (31.9°C–34.4°C) reflect the impact of detergents and urban runoff, threatening biodiversity and oxygen levels. Without intervention, the river's pollution will escalate, posing ecological and health risks. Sustainable strategies, including better wastewater treatment, stricter industrial regulations, and community-based waste management, are essential for long-term water quality sustainability.